2014
DOI: 10.2136/sssaj2014.05.0218
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Model for Estimating Soil Thermal Conductivity from Texture, Water Content, and Bulk Density

Abstract: Soil thermal conductivity (λ) models are needed frequently in studying coupled heat and water transfer in soils. Several models are available, but some are complicated and some produce relatively large errors. In this study, we developed a simple model for estimating λ from soil texture, bulk density (ρb), and water content (θ). Three parameters, α, β, and λdry, are included in the model, where λdry is determined by ρb and α and β are shape factors estimated from soil texture and ρb. Empirical relations were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
106
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 25 publications
4
106
0
Order By: Relevance
“…Based on soil water content and thermal conductivity datasets, Lu et al () presented an empirical model relating λ to θ , ρ b and soil texture, as follows: λ=λdry+exp()βθα,θ>0, where α and β were factors that affected the shape of the λ ( θ ) curve. They were estimated from soil particle‐size information and ρ b : {-13.5emα=0.67fcl+0.240.25emβ=1.97fsa+1.87ρb1.36fsaρb0.95, where f cl and f sa were USDA‐fractions of clay and sand, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on soil water content and thermal conductivity datasets, Lu et al () presented an empirical model relating λ to θ , ρ b and soil texture, as follows: λ=λdry+exp()βθα,θ>0, where α and β were factors that affected the shape of the λ ( θ ) curve. They were estimated from soil particle‐size information and ρ b : {-13.5emα=0.67fcl+0.240.25emβ=1.97fsa+1.87ρb1.36fsaρb0.95, where f cl and f sa were USDA‐fractions of clay and sand, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…the slope of the λ ( θ ) curve), whereas the β parameter influenced the magnitude of λ . Additional details about the model can be found in Lu et al ().…”
Section: Methodsmentioning
confidence: 99%
“… λ s and k s of the soil samples were then determined in the laboratory (about 20°C) at different fractions of volumetric water content ( θ ) when the samples were dried in an oven (blue circles in Figure ). Multiple studies have suggested an exponential relationship between the thermal properties and θ [ McCumber and Pielke , ; Chen and Dudhia , ; Wang et al , ; Guan et al , ; L. Wang et al , ; Lu et al , ]. Following an empirical relationship proposed in Lu et al [], the best fit relationship between λ s (W m −1 K −1 ) and θ , as shown in Figure a, can be described as λs=0.20+exp()1.46θ0.34, where 0.20 W m −1 K −1 is the thermal conductivity of dry soil and 1.46 and 0.34 are shape factors of the fit curve, which are fitted using a global optimization algorithm [ Vrugt et al , ].…”
Section: Experimental Setup Data and Evaluation Toolsmentioning
confidence: 99%
“…Following an empirical relationship proposed in Lu et al [], the best fit relationship between λ s (W m −1 K −1 ) and θ , as shown in Figure a, can be described as λs=0.20+exp()1.46θ0.34, where 0.20 W m −1 K −1 is the thermal conductivity of dry soil and 1.46 and 0.34 are shape factors of the fit curve, which are fitted using a global optimization algorithm [ Vrugt et al , ]. Lu et al [] suggested that the shape factors vary with soil texture and bulk density; however, information about soil texture was not available for this study. Assuming a uniform soil texture in the 0–20 cm layer, equation was used to calculate λ s at each time step and at different depths.…”
Section: Experimental Setup Data and Evaluation Toolsmentioning
confidence: 99%
“…Hence, much effort has been made to develop models incorporating these soil parameters which can be evaluated from laboratory investigations (Mickley, 1951;Gemant, 1952;Woodside and Messmer, 1961;De Vries, 1963;Johansen, 1975;Campbell, 1985;Coté and Konrád, 2005;Lu et al, 2007;Lu et al, 2014). The majority of these empirical or semitheoretical relations need the soil solid thermal conductivity (λ s ) as an input parameter.…”
mentioning
confidence: 99%